Transaksi Cryptocurrency dalam Pandangan Hukum Ekonomi Syariah - Hardian Satria Jati; Ahmad Arif Zulfikar (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2021)
The increasingly widespread development of the digital era has led to changes in the payment system which then affects the economic behavior of the community in line with the increase in various services that facilitate economic activity. An example is the emergence of crypto currency or Cryptocurrency as a digital currency that has almost the same function as other currencies. The thing that distinguishes this digital currency from conventional currencies in general is that it does not have a physical form of money like currency currency but only a block of data bound by a hash as validation. Although it provides a number of advantages for its users, the existence of cryptocurrencies in Indonesia itself is still experiencing pros and cons in terms of regulation and legality, especially from the point of view of Islamic law for its use. Therefore, this study was conducted to review cryptocurrencies that are widely used in transactions, especially investments from the perspective of Islamic law. This research is a qualitative library research. The data analysis technique used is descriptive-analytical with a normative juridical approach to Islamic law. Based on a number of references used in this study, it is known that investing with cryptocurrencies has a very high risk because its value can go up or down drastically and unpredictable. Meanwhile, from the point of view of Islamic sharia law, the law of this cryptocurrency transaction is haram lighairihi.